Strategi Pengembangan Potensi Petatas (Ipomea Patatas L) Menjadi Tepung Di Kampung Bersehati Distrik Tanah Miring Kabupaten Merauke - Anam, Mohammad Choirul; Widiastuti, Maria Maghdalena Diana; simatupang, david oscar (Musamus University, 2018)
these activities were not sustainable. This study aims to identify various opportunities, strengths,weaknesses and threats, examine internal external factors, formulate and determine selected strategies indeveloping sweet potatos flour business using the SWOT matrix. Determination of selected strategies isdone using the QSPM matrix. The research was conducted from March to June 2018, in the pet flourprocessing business group of the Village of Salted District of Tanah Miring District of Merauke Regency.The results showed that IFAS (Internal Factor Summary) factors in the sweet potato flour business werethe availability of raw material for sweet potato, lack of equipment and use of technology, limitedavailability of capital, adequate human resources and less than optimal management. EFAS factor (ExternalFactor Summary) in the sweet potato flour business is the support of the village and communitygovernments very well, the market potential is quite good, price fluctuations, lack of competitiveness andthe role of the Government. The SWOT analysis formulated 11 (Eleven) alternative strategies fordeveloping sweet potato flour namely : 1; Collaborating with the Government through a work program tofunction, to operate and develop flour business 2; Improve marketing networks by adding marketingpartners 3; Promoting back to the community that sweet potato flour products are local products as superiorproducts of Merauke Regency 4; Organizing internal training sustainable business management (routinemeetings) 5; Requesting capital from the Government to advance business 6; Need to conduct an analysisof petroleum flour business studies 7; Establish attractive product promotion 8; Create (value added) forflour products. 9; Create and develop a system storage of raw materials 10: Conducting training on how tomanage business capital (financial management) 11; Increasing technology for preserving sweet potatoflour. Furthermore, based on the QSPM (Quantitative Strategic Planning Matrixs) matrix, there are 2 (two)alternatives that have the highest score as the first strategy done first 1: Collaborating with the Governmentthrough work programs to enable, to operate and develop sweet potato flour business, total alternativescores 5,12. And the last strategy that needs to be done is a study of the analysis of sweet potato flourbusiness, a total alternative score of 1,42.Keywords: QSPM analysis, SWOT matrix, development strategy, sweet potato flour